Long non-coding RNA DNMBP-AS1 promotes prostate cancer development by regulating LCLAT1. (4th March 2023) - Yin, Xiangang; Wang, Suying; Ge, Rong; Chen, Jinping; Gao, Youliang; Xu, Shanshan; Yang, Ting
Abstract: Prostate cancer (PCa) is as a serious threat to male's health around the world. Recent studies have indicated that long non-coding RNAs (lncRNAs) occupy an important position in various human cancers. However, the function and mechanism of lncRNA DNMBP antisense RNA 1 (DNMBP-AS1) in PCa is rarely investigated. RT-qPCR analysis was used to test gene expression. CCK-8, colony formation, EdU staining and transwell assays were conducted to assess the function of DNMBP-AS1 on PCa cell behaviors. RNA pull down, RIP and luciferase reporter assays were implemented to verify the mechanism of DNMBP-AS1. DNMBP-AS1 was obviously up-regulated in PCa cell lines. Functionally, DNMBP-AS1 knockdown weakened cell proliferation, migration and invasion of PCa. Mechanistically, DNMBP-AS1 sponged microRNA-6766-3p (miR-6766-3p) to regulate lysocardiolipin acyltransferase 1 (LCLAT1) expression. Furthermore, DNMBP-AS1 could stabilize LCLAT1 expression by recruiting ELAV like RNA binding protein 1 (ELAVL1). Consequently, rescue assays demonstrated that DNMBP-AS1 regulated PCa cell proliferation, migration and invasion through enhancing LCLAT1 expression. Collectively, we elucidated the function and regulatory mechanism of DNMBP-AS1 and provided the first evidence of DNMBP-AS1 as a driver for PCa.